Shifting subsistence patterns from the Terminal Pleistocene to Late Holocene: A regional Southeast Asian analysis. (20th September 2019) - Jones, Rebecca K.; Piper, Philip J.; Groves, Colin P.; Nguyễn Anh, Tuấn; Nguyễn Thi, Mai Huong; Nguyễn Thị, Hảo; Hiep Hoang, Trinh; Oxenham, Marc F.
Abstract: The emergence of agriculture in Mainland Southeast Asia appears to have resulted in a subsistence shift from hunting terrestrial and arboreal game to a combined hunting/animal management subsistence regime focused on the maintenance of pigs and dogs. These conclusions are currently based on nominal differences in vertebrate taxonomic composition observed at different archaeological sites. In this paper, we take a statistical approach to test whether hunter-gather and early agricultural subsistence economies really can be confidently distinguished based on the relative taxonomic composition of the recovered animal bone assemblages. A regional database of terrestrial and arboreal vertebrate faunas was created for 32 archaeological sites across Southeast Asia from the Terminal Pleistocene to the Late Holocene, and principal component analysis was performed. The resultant data indicates that terrestrial vertebrate taxonomic composition is a relatively strong indicator of the general subsistence base for the various archaeological sites studied and can be used to determine whether the inhabitants subsisted purely from hunting, or from a mixture hunting and animal management.